Understanding decision of pharmacy-owning pharmacists to enroll in the community pharmacy accreditation program in Nakhonratchasima province - Pongpaka Puntaluck (Chulalongkorn University, 2011)
Thesis (M.Sc.)--Chulalongkorn University, 2008